Perceptions of Altered Smile Esthetics: A Comparative Evaluation in Orthodontists, Dentists, and Laypersons - Amjad Al Taki; Mohammed Khalesi; Muftah Shagmani; Islam Yahia; Fatma Al Kaddah (Hindawi Limited, 2016)
Objective. The current investigation was proposed to determine the impression of trained dental professionals and laypeople towards the modified smile esthetics. Materials and Methods. Twenty-six images were randomized in a survey and graded according to attractiveness by the orthodontists, general dentists, and laypeople. Photographs of gingival display, midline diastema, central incisor crown length, and lateral incisor crown width were manipulated with five minor changes in each. For smile arc and buccal corridor, two major changes were incorporated besides the ideal photograph. One-way ANOVA and Post Hoc analysis of the responses were measured for each group. Results. Most evaluators opined that the ideal smile in each category was the most acceptable. Orthodontists were more perceptive and exacting in accepting variations in the smile arc and buccal corridors. Dental professionals and laypeople indicated that either complete absence or a 0.5 mm of alterations in a gingival display, midline diastema, and crown length makes a smile beautiful and pleasant. Changes in crown width were not perceivable by all the three groups. Conclusion. Eastern Arabic laymen are more conscious about alterations in gingival display, midline diastema, and crown length in their smile. Hence, the orthodontist should pay attention to these factors during any orthodontic treatment.